1998
DOI: 10.1177/0734242x9801600604
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hygiene in biowaste composting

Abstract: Source-separated biowastes from the Helsinki Metropolitan Area have been composted in open air windrows at Ammas suo, the Helsinki regional landfill in Espoo (Finland). The most significant problem encountered in the early stages of the process has been the formation of rancid odor causing human discomfort. The offensive odor was mainly due to car boxylic acids. A total of 110 organic compounds were detected in volatile emissions from windrow composts with an integrated sensory and instrumental method. Occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…1998). In spite of the high allergic potential related to these kinds of bacteria, the dispersion of mesophilic and thermophilic actinomycetes from composting plants has been considered in relatively few papers (Tolvanen et al. 1998; Folmsbee and Strevett 1999; Taha et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998). In spite of the high allergic potential related to these kinds of bacteria, the dispersion of mesophilic and thermophilic actinomycetes from composting plants has been considered in relatively few papers (Tolvanen et al. 1998; Folmsbee and Strevett 1999; Taha et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bioaerosol emission rate and dispersal at composting sites is influenced by a large number of factors, including materials being composted, on-site processes involved, associated vehicle movements, process equipment used, individual bioaerosol properties and geographical, topographical and meteorological conditions on-and off-site. Several studies have assessed bioaerosol exposure, originated from many activities, at and around composting facilities (Marchand et al 1995;Reinthaler et al 1997;Tolvanen et al 1998;Folmsbee and Strevett 1999;Hryhorczuk et al 2001;Lavoie and Guertin 2001;Taha et al 2005). In addition, some authors have observed significant differences of bacterial and fungal dispersion during low and high levels of composting activities (Jager et al 1994;Reinthaler et al 1997;Hryhorczuk et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Alkylated benzenes (toluene, ethylbenzene, xylene, styrene) were detected the highest relative concentrations from the poultry litter composting process. These compounds had been also identified by Wilkins (1994), Eitzer (1995), Tolvanen et al (1998), and Komilis et al (2004) in the headspace of mixed wastes.…”
Section: Time (Weeks) Vocs Emissions (Mg/mmentioning
confidence: 94%
“…The VOCs detected were typical of composting plants: carboxylic acids and their esters, some alcohols, ketones, aldehydes and terpenes (Wilkins, 1994;Hänni-nen et al, 2002;Tolvanen et al, 1998;Wilber and Murray, 1990). The overall odour was sour, sweet, a bit rancid and biowaste-like at both sampling sites.…”
Section: Volatile Organic Compounds and Olfactometric Measurementsmentioning
confidence: 94%